A comparison of numerical methods for the time domain modelling of pile driving noise in the near field - Wilkes, Daniel; Gourlay, Tim; Gavrilov, Alexander (Australian Acoustical Society, 2014)
This paper presents a comparison of numerical methods for the modelling of pile driving noise in the near field of the pile. The numerical models considered consist of (1) an axisymmetric time domain finite difference method (FDM), developed by the Centre for Marine Science and Technology in the Matlab programming language, and (2) an axisymmetric time domain finite element method (FEM), which is available as part of the PAFEC–FE commercial software suite. The FDM employs thin-shell theory to model the cylindrical steel pile and the acoustic wave equation to model the water and fluid seabed, while the FEM employs the elastic and acoustic wave equations to model sound propagation in the pile and water/fluid seabed respectively. Aone–way coupling of the pile displacements to the fluid pressures is utilised in the FDM to model the acoustic radiation from the pile excitation, while the FEM employs a fully coupled fluid-structure interaction at the solid–fluid interface. Numerical results for both models are presented in the form of pile radial displacement results and pressure results in the near field of the pile. Good agreement is observed between the FDM and FEM models, while the FDM is observed to be at least twice as fast as the FEM for the considered models.